Recreational Water Safety in Hotels: Lessons from the COVID-19 Pandemic and the Way Forward for a Safe Aquatic Environment - Antonios Papadakis; Dimosthenis Chochlakis; Eleftherios Koufakis; Vilelmine Carayanni; Anna Psaroulaki (Tourism and Hospitality)
The recreational waters of hotels are widely used by locals and travelers all around the world, and this impacts public health. In this regard, the WHO frequently offers recommendations—especially during the COVID-19 era—that operators and managers of public pools, hot tubs, or splash pads should continue to follow. This study aims to evaluate the microbiological results of COVID-19 sanitation protocols in recreational waters in hotels during the summer periods post-COVID-19 (2020–2022) and compare them with those pre-COVID-19 (2019). Of the samples tested during the pre-pandemic period, less than 1/5 were positive for total coliforms, common aerobic bacteria, and P. aeruginosa, while less than 3% of the samples tested were positive for E. coli. During the pandemic years, the percentages dropped by half for total coliforms, common aerobic bacteria, and E. coli, while only the percentage for P. aeruginosa remained the same. The relative risk (RR) for the presence of P. aeruginosa in recreational waters was greatly affected by chlorine levels, pH values, and water temperature. Our results elucidate the impact of sanitation protocols on the safety of recreational waters in hotels during public health crises. Moreover, the challenges operators face in maintaining long-term implementation of these protocols are highlighted, which in turn dictates the appropriate choice of preventive and applicable measures to ensure health and safety.